The Influence of Exogenous and Endogenous Factors on the Individual Characteristics of Students - Mannonovna, Rahimova Madina; Mansurbekovna, Kengesbaeva Umida (American Journal of Bioscience and Clinical Integrity, 2025)
Exogenous psychoses are a group of mental disorders united by a common etiology (infections, intoxications, traumatic brain injuries, etc.), features of clinical manifestations, course and consequences. In this sense, they can be contrasted with endogenous mental disorders, although such a difference is relative, since, on the one hand, there is evidence of the significant role of endogenous factors (heredity, age, constitutional features, etc.) in the occurrence of exogenous psychoses, and, on the other hand, of the importance of external risks in determining and determining the genetic predisposition of the disease. The only absolutely reliable difference is the presence of an organic (brain) substrate of the disease, which can be detected by paraclinical methods.